2021
DOI: 10.1055/s-0040-1715606
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Vestibular Schwannoma: A Systematic Literature Review

Abstract: Objective Ipsilateral cochlear implantation (CI) in vestibular schwannoma (VS) has been an emerging trend over the last two decades. We conducted the first systematic review of hearing outcomes comparing neurofibromatosis 2 (NF2) and sporadic VS undergoing CI. A comparison of the two populations and predictor of outcome was assessed. This is an update to a previously presented study. Data Sources Systemic data searches were performed in PubMed NCBI and Scopus by an academic librarian. No restrictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…17,18 However, CI can only be provided if the CN function can be preserved. 6,19 While assessment of CN function has proven difficult in the past, the advent of intraoperative eABR measurements allowing meticulous monitoring of CN function has opened up plenty of opportunities to improve optimal screening and selection of patients eligible for CI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, CI can only be provided if the CN function can be preserved. 6,19 While assessment of CN function has proven difficult in the past, the advent of intraoperative eABR measurements allowing meticulous monitoring of CN function has opened up plenty of opportunities to improve optimal screening and selection of patients eligible for CI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent improvements in MRI sequencing and cochlear implant magnet design significantly reduce the severity of metal artifacts in MRI, which would normally hinder the appropriate postoperative tumor follow‐up with a cochlear implant in place 17,18 . However, CI can only be provided if the CN function can be preserved 6,19 . While assessment of CN function has proven difficult in the past, the advent of intraoperative eABR measurements allowing meticulous monitoring of CN function has opened up plenty of opportunities to improve optimal screening and selection of patients eligible for CI.…”
Section: Discussionmentioning
confidence: 99%
“…However, these reviews will often combine both operated and observed tumors, making outcome comparisons difficult. Tadokoro et al (63) reviewed CI in patients with VS and compared outcomes between sporadic and NF2-associated tumors. Fifty-six percent of tumors in their review had undergone resection before CI.…”
Section: Vestibular Schwannomasmentioning
confidence: 99%
“…The majority of CI outcome data in VS come from the NF2-related schwannomatosis (formerly neurofibromatosis type 2, hereafter referred to as “NF2”) literature (5). This is because subjects with NF2 often acquire bilateral nonserviceable hearing as a result of the disease process or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cochlear implants (CIs) are one option to rehabilitate hearing in select patients with a sufficiently healthy intact cochlear nerve (2)(3)(4). Several studies have shown success with cochlear implantation in this population, generally with improved outcomes compared with auditory brainstem implantation (2)(3)(4)(5)(6). Although studies are limited, some have also stratified CI outcomes according to treatment modality to inform treatment algorithms for VS with long-term hearing in mind (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%